The Aspects of the Development of Children Speech in their Constructive Activity - Aizporaite, Ineta (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
One of the most important task of the pre – school pedagogical process is to promote the development of the chidren thinking and imagination. One of the method is the constructive activity whick aim is to develop the children abstractive thinking and imagination. Constructive activity concerns several children processes of cognition, it promotes the perceptivities, thinking, imagination, understanding of the environment, it makes the child to think of the colours, shapes and connections of the items. Construction promotes the development of the speech, it introduces children with mathematical conceptions and the base of geometry. Wider conceptions and understanding about the construction activities form on the base of practical experience, in the concrete in direct contact with construction materials. Performing researches, analysing the literature we can make conclusions about the significance of the intellectual and mental age, psychogical factors and environment in constructive activity.